Proceedings of the 2010 ACM-IEEE International Symposium on Empirical Software Engineering and Measurement 2010
DOI: 10.1145/1852786.1852841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimized staffing for feature development and bug fixing

Abstract: Skill level and productivity varies substantially between developers. In current staffing practices, however, developers are largely treated as the same. In this paper, an empirical analysis of the tow formulations of assignment of developers to tasks and bug fixing activities is studied. Two related problems are considered:(i) Assignment of developers to bug fixing with the objective to achieve best match between requested skill profile and assigned developer's skill profile.(ii) Assignment of developers to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Before we proposed a GA‐based approach for assigning developers to bugs , the K‐greedy approach , a greedy‐based technique, was one of the three automatic approaches for assigning developers to bugs. Given a bug's arrival (filing) time, this algorithm considers all the developers who are available at and after that time (until a time window called the look‐ahead time (LAT)).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Before we proposed a GA‐based approach for assigning developers to bugs , the K‐greedy approach , a greedy‐based technique, was one of the three automatic approaches for assigning developers to bugs. Given a bug's arrival (filing) time, this algorithm considers all the developers who are available at and after that time (until a time window called the look‐ahead time (LAT)).…”
Section: Related Workmentioning
confidence: 99%
“…Rahman et al proposed a GA‐based approach for developer's assignment to bugs. Our bug assignment approach has some differences compared with their approach.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Kang et al (2011) optimized the scheduling of human resource allocations by using a variant of SA, taking into account individual and team constraints based on the literature and interviews with experts in the industry, and by employing real data to validate their proposal. Rahman et al (2010) also reported on an empirical analysis carried out exploiting real data on the use of both GA and a greedy approach that makes the locally optimal choice at each stage to assign developer to tasks and bug fixings activities. Different aspects of the management also focused on the allocation of staff (Barreto et al 2008) (Kapur et al 2008) and the provision of decision support (Cortellesa et al 2008).…”
Section: Minimising Software Project Completion Timementioning
confidence: 99%